ANALISIS KARAKTERISTIK CAMPURAN ASPAL PANAS DENGAN MENGGUNAKAN CAMPURAN ASPAL REJECT - Gunawan, I Wayan; Thanaya, I Nyoman Arya; Purbanto, I Gusti Raka (Jurnal Ilmiah Teknik Sipil, 2016)
Natural road materials are not renewable, but they can be reused. In long term it is getting more difficult to obtain natural materials; therefore alternative materials are needed for road pavement. Within this experiment, it was used reject asphalt mixture as the main material and added with some coarse aggregate, fine aggregate, filler and asphalt emulsion. The aim of this experiment is to analyze the properties of Asphalt Concrete Binder Course (AC-BC), that utilize reject asphalt mixture as the main material and added with asphalt emulsion. The asphalt content of the reject asphalt mixture was 7.2%. The optimum asphalt content of the AC-BC was 6.2% by weight of total mixture (with 0.9% added residual asphalt emulsion towards the weight of the reject asphalt mixture). The properties of the AC-BC at its optimum 6.2% asphalt content with 2x75 Marshall blows was: stability 3027,07 kg (spec ? 800kg); flow 4,29 mm (spec ? 3); Marshall Quotient 716,09 kg/mm (spec ? 250); VIM 4,05% (spec 3,0%-5%); VMA 15,349% (spec ? 14) and VFB 73,589% (spec ? 63). There is a possibility that the time for mixing of asphalt mixture during production on site is longer than it should be, due to problem on transportation which can cause hardening of the asphalt binder. This situation is simulated by doing STOA ( short term oven ageing ) test. The properties of the AC-BC above after STOA treatment gives: stability of 1658,56 kg, flow 3,98 mm, Marshall quotient 435,39. Meanwhile the VIM, VMA and VFB are respectively 4,54%; 15,447% dan 70,589%, all meet the specification.
Keywords: AC-BC, Reject Asphalt, Marshall